2013
DOI: 10.5402/2013/478192
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Desires and Intentions and the Relationship to Consistent Condom Use and Provider Communication regarding Childbearing among HIV Clients in Uganda

Abstract: Objectives HIV prevention and reproductive health programs emphasize consistent condom use and preventing unplanned pregnancies, but do not account for the childbearing desires of many HIV clients. We examined the correlates of fertility desires and intentions, including condom use, among HIV clients in Uganda. Methods Baseline data from a prospective cohort study of clients starting antiretroviral therapy were analyzed. All measures were self-report, except abstracted CD4 count. Results The sample include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 31 publications
4
45
3
Order By: Relevance
“…These findings therefore provide important insights into the social and clinical correlates of reproductive health behaviours and the service needs of PLHIV attending HIV clinical care. Only 17% of participants reported desiring a pregnancy in the next 6 months, an estimate lower than other studies among PLHIV in sub-Saharan Africa including studies from Nigeria (63%), Tanzania (37%), Uganda (31%) and South Africa (29%), 151739 but higher than estimates from Uganda (8%) and Rwanda (8%). 3137 Significant correlates of fertility desire included being currently married, having fewer children, and being in a recent relationship.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…These findings therefore provide important insights into the social and clinical correlates of reproductive health behaviours and the service needs of PLHIV attending HIV clinical care. Only 17% of participants reported desiring a pregnancy in the next 6 months, an estimate lower than other studies among PLHIV in sub-Saharan Africa including studies from Nigeria (63%), Tanzania (37%), Uganda (31%) and South Africa (29%), 151739 but higher than estimates from Uganda (8%) and Rwanda (8%). 3137 Significant correlates of fertility desire included being currently married, having fewer children, and being in a recent relationship.…”
Section: Discussioncontrasting
confidence: 60%
“…3137 Significant correlates of fertility desire included being currently married, having fewer children, and being in a recent relationship. Other studies have also found that having fewer children 1519222337 and duration of relationship 16 were important predictors of fertility desire among PLHIV.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In sub-Saharan Africa, the main mode of HIV transmission is through heterosexual sex with a concomitant epidemic in children through vertical transmission [4]. Despite the risk of mother to child transmission of HIV, significant proportion of parents living with HIV continued to desire to have children [5][6][7][8]. Studies also revealed that HIV-positive women encountered unintended pregnancies with associated risk of mother to child transmission of HIV [9][10][11].…”
Section: Introductionmentioning
confidence: 99%